Advances in health care management. Vol. 3 - Fottler, Myron D.; Savage, Grant T. 1954-; Blair, John D. 1944- (Advances in health care management., 2002)
List of contributors. Review board members. Reviewers. Advances in health care management: overview (G.T. Savage et al.). Special Research Forum on Management Issues in Nursing. Nurse staffing and nursing performance: a review and synthesis of the largely unexplored relationship (L.Y. Unruh, M.D. Fottler). The benefits of staffing and paying more: the effects of staffing levels and wage practices for registered nurses on hospitals' average lengths of stay (M.P. Brown et al.). The impact of workplace empowerment, organizational trust on staff nurses' work satisfaction and organizational commitment (H.K. Spence Laschinger et al.). Managing routine exceptions: a model of nurse problem solving behavior (A. Tucker, A.C. Edmondson). Clinical and Technological Issues in Health Care Management. Population health management in theory and practice (A. Scheck Mcalearney). Emotions, the neglected side of patient-centered health care management: the case of emergency department patients waiting to see a physician (L. Dube et al.). Innovation in medical devices and medical electronics: are European regulations and practices shifting innovation to Europe? (D.F. Robinson). Organizational and Strategic Issues in Health Care Management. Managers' perceptions of hospital capabilities: a theoretical and empirical study (A. Wilcox King, C.P. Zeithaml). Management of academic health centers: the past, present, and future (S. Topping, D. Malvey). A strategic change/organizational ecology based theory of post-bankruptcy performance in healthcare firms (D.D. Dawley et al.). From stakeholder management strategies to strategic styles: serendipitous research on organizational configurations (J.D. Blair et al.).